Variable joint accessory - CHEN KUNYING; ZHONG LINZHI; CAO YIDONG (2025)
The utility model discloses a variable joint accessory which is of an integrally-formed structure and comprises an input pipe joint capable of being used as a bell mouth and an output pipe joint capable of being used as a spigot. The input pipe joint and the output pipe joint are connected through a plurality of middle pipe joints and a plurality of transition pipe joints, the middle pipe joints and the transition pipe joints are arranged at intervals, the outer diameter of the middle pipe joints is consistent with the outer diameter of the output pipe joint, the middle pipe joints can serve as inserting openings, and the axes of the middle pipe joints, the axis of the input pipe joint and the axis of the output pipe joint are all located on the same plane. From the input pipe section to the output pipe section, the included angle between the axis of the input pipe section and the axis of the middle pipe section is gradually increased; the end, away from the input pipe joint, of the middle pipe joint is fixed